Proptech (Properti Techology) Sebagai Solusi Penyewaan Properti Jangka Pendek Berbasis Online - Christian Tobing; Monika Haning; Tjie Tjung; Dimas Satria Sidiqurrohman; Rizani Candra Sirait (Journal Of Business, Finance, and Economics (JBFE), 2024)
This research aims to analyze the business planning strategy of Proptech companies in facing the increasing trend of rental property demand in Jakarta, as well as the challenges faced by tenants and property owners regarding the less flexible rental payment system. This research uses a qualitative approach with a case study method, collecting data through in-depth interviews, observation, and documentation studies. The analysis was conducted through input, matching, and decision stages using EFE, IFE, and CPM matrices to evaluate internal and external factors affecting business strategy. The results show that Proptech responds well to opportunities and threats in the market, with an EFE score of 3.03 and an IFE of 2.93, indicating a strong internal position and adaptability to external conditions. Alternative strategies proposed include the development of a more flexible rental payment system to attract more tenants, as well as the expansion of services to more cities. In conclusion, with the right strategy, Proptech can take advantage of existing opportunities to strengthen its position in the market, as well as overcome challenges in the property rental payment system, so as to increase competitiveness and meet market needs.